An integrated analysis of C5AR2 related to malignant properties and immune infiltration of gliomas. Issue 3 (5th October 2022) - Huang, Chengying; Qiu, Ouwen; Mao, Chaofu; Hu, Zhicheng; Qu, Shanqiang
Abstract: Background: C5AR2 is recognized as a proinflammatory molecule and activates the inflammatory response in multiple disorders. However, little has been reported on C5AR2 in glioma. This study sought to explore its expression, biological function, and association with clinical pathological indicators, prognosis, and immune infiltration levels in glioma through glioma cohorts. Methods: A cohort of 657 patients was screened from the Chinese Glioma Genome Atlas (CGGA). χ 2 test was performed to calculate the difference of classified variables. Cox proportional hazard regression modeling was used to identify independent prognostic indicators of glioma patients. A survival plot was generated by the Kaplan–Meier method. The immune cell infiltration score of glioma patients was calculated by TIMER algorithm. Results: We observed that high expression of C5AR2 was strongly associated with malignant clinical indicators in 657 patients with glioma, and patients with high C5AR2 expression had worse prognoses. Multivariate Cox analysis showed that C5AR2 could be a new independent prognostic indicator for glioma patients. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis revealed that C5AR2 overexpression correlated with multiple inflammatory and immune biological processes. Additionally, high C5AR2 expression was strongly associated with higher abundance and marker gene expression of multiple tumor immune cells in low‐grade glioma. Finally, a model was constructed to improve the prognostic evaluation of glioma patients. Conclusions: The C5AR2 gene is highly expressed in gliomas and is significantly associated with clinical indicators of malignant progression in glioma patients. In glioma, patients with high C5AR2 expression displayed a worse outcome. In glioma tissues, the expression level of C5AR2 highly correlated with the abundance of tumor immune cell infiltration. Additionally, GO and KEGG enrichment analysis revealed that C5AR2 expression may be involved in a variety of immune and inflammatory biological processes. Abstract : C5AR2 in not only a prognostic biomarker, but also may play a key role in controlling tumor immune microenvironment in gliomas. These findings suggest that C5AR2 is a potential prognostic marker and immunotherapeutic target in glioma.